2020
DOI: 10.1177/0003489420938821
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of Research by Matched Otolaryngology Residency Applicants

Abstract: Objectives: Matching to an otolaryngology residency program is a competitive process for medical students, and research performed by students is considered as a factor for granting interviews by program directors. Because abstracts, presentations and publications are all reported in combination by the National Resident Matching Program’s “Charting Outcomes in the Match” (ChOM) and may be weighted differently by PDs, we specifically investigated the number of publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…Other groups have utilized bibliometric analyses to study the importance of research in matching to other competitive and similarly research-heavy specialties, such as neurological surgery, otolaryngology, and plastic surgery. 8 , 9 , 10 , 11 Prior studies have differed slightly in methodology and findings, with 1 reporting only h -index to correlate significantly with matriculating to higher-tier residencies, 8 while another found both h -index and total number of publications to be significant. 9 In general, these studies also found that increased research productivity during medical school correlated with matching at higher-tier residency programs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other groups have utilized bibliometric analyses to study the importance of research in matching to other competitive and similarly research-heavy specialties, such as neurological surgery, otolaryngology, and plastic surgery. 8 , 9 , 10 , 11 Prior studies have differed slightly in methodology and findings, with 1 reporting only h -index to correlate significantly with matriculating to higher-tier residencies, 8 while another found both h -index and total number of publications to be significant. 9 In general, these studies also found that increased research productivity during medical school correlated with matching at higher-tier residency programs.…”
Section: Discussionmentioning
confidence: 99%
“… 9 In general, these studies also found that increased research productivity during medical school correlated with matching at higher-tier residency programs. 8 , 9 , 10 , 11 The protocols used for data identification, collection, and statistical analysis in these studies were modified and refined to implement the best approach to assess research productivity in radiation oncology residents. For example, 2 studies of residents in neurological surgery and otolaryngology used univariate and multivariate statistical analysis, but data were collected only from Scopus, and the respective residency programs were ranked based only on research output.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations